2011
DOI: 10.1038/nsmb.2171
|View full text |Cite
|
Sign up to set email alerts
|

Structure of green-type Rubisco activase from tobacco

Abstract: Rubisco, the enzyme that catalyzes the fixation of atmospheric CO(2) in photosynthesis, is subject to inactivation by inhibitory sugar phosphates. Here we report the 2.95-Å crystal structure of Nicotiana tabacum Rubisco activase (Rca), the enzyme that facilitates the removal of these inhibitors. Rca from tobacco has a classical AAA(+)-protein domain architecture. Although Rca populates a range of oligomeric states when in solution, it forms a helical arrangement with six subunits per turn when in the crystal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
275
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(292 citation statements)
references
References 43 publications
14
275
3
Order By: Relevance
“…Proteins were purified as described in SI Materials and Methods. Rubisco and ATPase activity was measured using coupled spectrophotometric assays (34,49). Inhibited rubisco complexes were prepared as described in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were purified as described in SI Materials and Methods. Rubisco and ATPase activity was measured using coupled spectrophotometric assays (34,49). Inhibited rubisco complexes were prepared as described in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…3). While differences between the two polypeptides are distributed throughout the protein, residues affecting nucleotide binding are likely to fall within the AAA+ motif (Henderson et al, 2011;Stotz et al, 2011). Also, it is likely that ADP sensitivity is conferred by a residue(s) outside the Rubisco recognition domain, since Rca activity in leaf extracts of the Arabidopsis Tob-DAt (S2) transformant was inhibited by physiological ratios of ADP to ATP (Fig.…”
Section: Adp Inhibition Of Recombinant B-rca Atpase Activitymentioning
confidence: 99%
“…3). No changes were made in the N-terminal domain because previous studies have shown that removal of the first 50 residues of the tobacco Rca does not affect ATP binding or hydrolysis (van de Loo and Salvucci, 1996;Stotz et al, 2011). The mutated enzyme, designated Tob-DAt (n=17) , catalyzed ATP hydrolysis at rates equivalent to wild-type tobacco b-Rca but was much less sensitive to inhibition by ADP, more closely resembling the Arabidopsis than the tobacco b-Rca (Fig.…”
Section: Adp Inhibition Of Recombinant B-rca Atpase Activitymentioning
confidence: 99%
“…4 shows low resolution 3D-structure of the Nicotiana tabacum RCA complex obtained by electron microscopy (PDB ID: 3ZW6). 48 The a-isoform differ from the b-isoform by the presence of a short C-terminal disordered extension that in most cases contains 2 cysteine residues, and is light dependent. 49 It was also pointed out that of these 2 isoforms, the longer RCA variant possesses higher ADP/ATP sensitivity, 50 but this high sensitivity is mostly eliminated via thioredoxin-f-induced reduction likely leading to the formation of a disulfide bridge between the C-terminal cysteine residues.…”
Section: Rubisco and Rubisco Activase (Rca)mentioning
confidence: 99%
“…51 Zhang et al (2001) indicated that RCAs are functional heteromers (a n b n ) and not homomers (a n or b n ), 46 and Stotz et al (2011) who worked with Nicotiana tabacum RCA found that the active state of this protein is a hexamer, where the helical insertion of the C-terminal is implicated in RuBisCO recognition and the Loop segments exposed toward the central pore of the hexamer required for the ATP-dependent remodeling of RuBisCO. 48 Based on this observations, Thieulin-Pardo et al (2015) proposed a model for RCA in for A.thaliana.…”
Section: Rubisco and Rubisco Activase (Rca)mentioning
confidence: 99%